1968
DOI: 10.1071/ch9681267
|View full text |Cite
|
Sign up to set email alerts
|

Meisenheimer salts. II. Stabilities and spectra of some metal methoxide adducts with anisoles

Abstract: N.m.r. spectral studies demonstrated that Meisenheimer salts were formed by addition of alkali metal methoxides to 4-cyano-2,6-dinitroanisole, 4-methoxy-3,5-dinitropyridine, and 2,6-dinitroanisole, but not with 2-methoxypyrimidine. Crystalline salts were isolated after addition of methoxide to the cyanodinitroanisole and methoxydinitropyridine. The stabilities of the Meisenheimer salts were found to be heavily dependent on the ability of ring substituents to accept negative charge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1968
1968
1982
1982

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Foster and Hainmick (1) assigned bands at 1492 and 1291 cm-I in potassium ethyl I-methoxypicrate to N-O antisymmetric and symmetric stretches, respectively. The corresponding frequencies of the parent nitro compound were 1552 and 1343 cm-l. Dyall and co-workers (4)(5)(6), in studies of Meisenheimer adducts of a'series of picryl ethers, seem to concur with these assignments. They suggest further that the covalent structure 1 should show the characteristic bands of a ketal (25) at 1195-1 158, 1143-1 124, 1098-1063, and 1058-1038 cm-' and consequently assign the strong bands of the adducts in the region 1300-1000 cm-' to this source.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Foster and Hainmick (1) assigned bands at 1492 and 1291 cm-I in potassium ethyl I-methoxypicrate to N-O antisymmetric and symmetric stretches, respectively. The corresponding frequencies of the parent nitro compound were 1552 and 1343 cm-l. Dyall and co-workers (4)(5)(6), in studies of Meisenheimer adducts of a'series of picryl ethers, seem to concur with these assignments. They suggest further that the covalent structure 1 should show the characteristic bands of a ketal (25) at 1195-1 158, 1143-1 124, 1098-1063, and 1058-1038 cm-' and consequently assign the strong bands of the adducts in the region 1300-1000 cm-' to this source.…”
Section: Discussionsupporting
confidence: 55%
“…Infrared studies have been reported on a wide variety of solid adducts precipitated from concentrated solutions containing an aromatic nitro compound and a suitable base (1)(2)(3)(4)(5)(6)(7)(8). Although the infrared spectra are in accord with the formulation of theseadducts as a-com~lexes.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in Me2SO it leads to the a complex 54, whereas in methanol the immediate product is the 1:2 a complex 55 (X = H).122 In the opinion of the authors,122 this is due to the fact that Me2SO better solvates the former and methanol the latter a complex.…”
Section: B Anionic a Complexes With Sulfur-containing Nucleophilesmentioning
confidence: 99%
“…The isolation of the 1,l-complex of the former compound has also been reported by other workers (see above). 204 The bright red colour formed on the addition of sodium hydroxide to an acetone solution of l-(~-hydroxyethoxy)-2,4-dinitrobenzene20s was thought to be due to the formation of a spiro-Meisenheimer complex (58).…”
Section: Ome No2 Omementioning
confidence: 99%